Industrialized building system : the government's effort and contractors' response - Ahmad Firdaus bin Baharuddin (Kulliyyah of Architecture & Environmental Design, International Islamic University Malaysia, 2015)
The main problem for construction industry in Malaysia is the late delivery of projects. Due to late delivery of projects, the Government has introduced various strategies to ensure the delivery of projects right on time, as stipulated in the construction contracts. For projects worth more than RM10 millions, the Government has imposed the use of Industrialized Building System (IBS). Although, the Government has done a lot of promotions and efforts towards encouraging the use of IBS system, however, the contractors' response towards it is vital to improve the future of our construction industry. This research is carried out by circulating sets of questionnaires to contractors who are registered with Construction Industry Development Board (CIDB). The focus is given to Grade G7 contractors because they are entitled to bid for work starting RM10 million and above. Secondary data is collected from IBS Centre and through some reading from industry publications such as ICU Weekly Performance Report, IBS Digest and others. Some of the data related to IBS system is collected through communications with industry experts and professionals. Most of the respondents are Bumiputra. They have undertaken three (3) or less IBS projects. Almost 90 percent of completed projects come from public sector development plans. From the survey, it is found that 71.3 percent preferred the use of pre-cast concrete system followed by pre-fabricated timber system with 13.9 percent. Only 47.8 percent of projects complied with the minimum requirement IBS score of 70 points and above. 65.2 percent of respondents did not know about Treasury Circular imposing the use of IBS system. 71.3 percent agreed that through their experience, the use of IBS system was moderate. However, most of the respondents agreed that IBS method will succeed in the future between the year 2016 to 2020.